A study of biological aspects of the krill population (Euphausia Superba Dana, 1892) at northern South Georgia Island in July-October 2001 - Savych, M. S.; Zhuk, N. N. (Ukrainian Antarctic Journal, 2004)
We consider the biological state of Antarctic krill Euphausia superba inhabiting the shelf and the slope at northern South Georgia Island in poorly investigated winter (July-August) and spring (September-October) months of 2001. According to the results of the research two size groups were distinguished – juveniles and mature individuals, characterized by seasonal variability of morphophysiological parameters as well as negative features – resorption of spermatophores in males and krill’s disease of soft tissues.